A note on the detection of the carrot weevil in Nova Scotia - LeBlanc, J.-P.R.; Boivin, G. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1993)
The carrot weevil, Listronotus oregonensis [Coleoptera: Curculionidae], is a significant pest of vegetable crops in northeastern North America. However, the species had not been previously detected in Atlantic Canada. In 1985,1986, and 1988, attempts to detect this pest in Nova Scotia were unsuccessful. In 1992, in one of three carrot (Daucus carota) fields monitored using thigmotactic wooden-plate traps baited with fresh carrots, six individuals were captured during the spring migration of the inseetfrom overwintering sites into a carrot field near Great Village, Nova Scotia.